Melodi Ilahi: Membongkar Keindahan Stilistika al-Mustawa al-Shauti dalam Surat Ad-Dhuha - Wildan Rinanda Komara; Rizzaldy Satria Wiwaha (Diwan: Jurnal Bahasa dan Sastra Arab, 2024)
This research aims to analyze the stylistics of the Ad Dhuha letter in relation to al-Mustawa al-Shauti. It is a type of library research that relies on data from written sources. The method used is content analysis. The results of this research reveal that there is harmony in each part of the verse. The distinctiveness and uniqueness of the sound in Surah Ad Dhuha is dominated by syllables with the arrangement consonant - vowel - consonant - long vowel (c v c v v). From the perspective of consonant types, it is dominated by semivowel consonants in the form of the letter alif maksurah (?), which is repeated eight times in verses 1-8.